Sarcopenia predicts immune-related adverse events due to anti-PD-1/PD-L1 therapy in patients with advanced lung cancer - Xue, Dinglong; Li, Ning; Yang, Jiaxin; Men, Kaiya; Li, Lijun; Jiang, Hao; Zhao, Xu; Zhang, Shuai (Frontiers in Oncology, 2024)
IntroductionImmune checkpoint inhibitors (ICIs) have revolutionized the treatment of a number of patients with advanced cancer, and while this has resulted in increased survival times, it has also led to the emergence of novel immune-related adverse events (irAEs). In individuals with advanced cancer, sarcopenia is a significant symptom of cachexia and is linked to poor nutritional status and increased mortality. The present study aimed to evaluate sarcopenia and other risk variables that can affect the emergence of irAEs in patients with lung cancer.MethodsA single-center retrospective analysis of 129 patients with advanced lung cancer treated with programmed cell death protein-1 (PD-1)/programmed cell death ligand-1 (PD-L1) checkpoint inhibitors was conducted from August 2020 to August 2022. Data on baseline characteristics and adverse events of participants were collected. Computed tomography was used to determine the skeletal muscle index at the third lumbar vertebra (L3-SMI) and whether sarcopenia is present.ResultsThe median age of all participants was 60 years old (range, 52-66 years), with men accounting for 68.9% of the total patient cohort. The present study showed that 44 (34%) participants presented with any degree of irAEs, and 79 (61.2%) patients presented with sarcopenia. There were no statistically significant differences in baseline characteristics, such as age and sex, between patients who presented with irAEs and those without irAEs. Using logistic regression analysis, individuals with sarcopenia were 2.635-times more likely to experience any grade of irAEs than those without sarcopenia.DiscussionirAEs are prevalent side effects of PD-1/PD-L1 inhibitor therapy for patients with cancer. By diagnosing and treating sarcopenia early, it is possible to lower the potential risk of irAEs in patients with advanced cancer. Furthermore, sarcopenia can be utilized as a predictor of irAEs.